Vernacular landscape and its role in the development of creative urban practices - Y. O. Butsykina (Ukrainian Cultural Studies, 2022)
The paper is devoted to the analysis of the vernacular landscape concept defined as one that is culturally conceptualized both within the city and outside it. We identified the key characteristics of the concept, such as: community, border, temporal development (Jackson), repetitive practices of non-professionals, variability and diversity (Certeau). We determined the key methods of cultural research of the vernacular landscape: representational and phenomenological. Representational method deals with the practices that refer to the repetitive habits and customs of the dwellers, everyday practices that are manifested in long-term fields studies and film and video materials stydying. We considered the peculiarities of vernacular landscape formation in the city and creativity as its essential characteristic. Accordingly, creative practices that shape the vernacular landscape of the city have the following defining features: inclusiveness, repeatability and familiarity, non-expertise, non-economic motivation. The nature of creativity itself allows the creative individual to directly influence the common good, changing the landscape of her locus (yard, district, city, etc.). The concept of tactical urbanism is considered as an alternative to the concept of creative economy and one that sees vernacular creative practices as a key engine for the development of creative potential of the city. This updated approach to understanding creativity significantly expands the term of vernacular landscape: both physically (because it expands the geography of creative practices of the city, going beyond certain areas, where the creative class is concentrated, up to the suburbs) and substantively (creative practices are interpreted in many more variable key). Creativity is singled out as one of the most common and revealing types of creative practices that have great potential in the qualitative transformation of the vernacular landscape of the city. Yarnbombing is a clear example of such a tactical intervention in urban space.